An Evaluation of a Suicide Prevention E-Learning Program for Police Officers (COPS): Improvement in Knowledge and Competence - Hofmann, Laura; Glaesmer, Heide; Przyrembel, Marisa; Wagner, Birgit (Frontiers in Psychiatry, 2021)
Background: Police officers are at high risk for mental and physical health problems and suicidal ideation. The specific risk factors are numerous and concern stressful missions and administrative aspects of the police profession. So far, the police get only little training on specific missions as well as on coping with stress and suicidal ideation in the police profession. In this study we test the efficacy of the online training COPS (Coping with Suicide) for police officers. Methods: A total of 142 police officers from Germany and Switzerland participated in the study; complete data (baseline and post) are available from 102 participants. The training consisted of three modules covering the topics of delivering death notifications, dealing with individuals with suicidal ideation and dealing with one's own distress and suicidal ideation in the police profession. The primary outcomes are perceived knowledge and self-rated competence regarding the contents of the program, actual knowledge as well as symptoms of depression and anxiety (PHQ-9), and attitudes towards suicide (ATTS). The data are collected at baseline and after completing the training. Results: We found a significant increase in knowledge as well as in perceived competence after completing the training. Mental health and attitudes towards suicide did not change significantly. Years on the job had no moderating effect on the effectiveness of the training. Discussion: The results suggest that a short e-learning program significantly improves knowledge and self-rated competence in delivering death notifications, in suicide prevention and stress management. It can be easily integrated into the daily routine of police-officers, and participants could participate at their own pace and from any location. One limitation of this study is the lack of a control-group. Further advantages and limitations of this study are discussed.